Copy number variation in mental retardation - Veltman, Joris (Henry Stewart Talks, 2009)
Genetics of mental retardation, Microarray-based detection of copy number variation (CNV), CNVs in mental retardation, a frequent cause, Molecular karyotyping, improving diagnostic yield
Archived at 2021/02/25